Negative affect predicts social functioning across schizophrenia and bipolar disorder: Findings from an integrated data analysis. (30th September 2016) - Grove, Tyler B.; Tso, Ivy F.; Chun, Jinsoo; Mueller, Savanna A.; Taylor, Stephan F.; Ellingrod, Vicki L.; McInnis, Melvin G.; Deldin, Patricia J.
Abstract: Most people with a serious mental illness experience significant functional impairment despite ongoing pharmacological treatment. Thus, in order to improve outcomes, a better understanding of functional predictors is needed. This study examined negative affect, a construct comprised of negative emotional experience, as a predictor of social functioning across serious mental illnesses. One hundred twenty-seven participants with schizophrenia, 113 with schizoaffective disorder, 22 with psychosis not otherwise specified, 58 with bipolar disorder, and 84 healthy controls (N= 404) completed self-report negative affect measures. Elevated levels of negative affect were observed in clinical participants compared with healthy controls. For both clinical and healthy control participants, negative affect measures were significantly correlated with social functioning, and consistently explained significant amounts of variance in functioning. For clinical participants, this relationship persisted even after accounting for cognition and positive/negative symptoms. The findings suggest that negative affect is a strong predictor of outcome across these populations and treatment of serious mental illnesses should target elevated negative affect in addition to cognition and positive/negative symptoms. Highlights: Large sample size ( N =404) used to investigate negative affect transdiagnostically. Negative affect explains outcome variance independent of traditional predictors. Negative affect may be a critical treatment target across serious mental illnesses.